YPAC Pangkalpinang Special School Branding Efforts through Teacher Mentoring to Improve Student Content Creator Skills - Irawadi, Syafrul; Maxrizal, M; Febriyansyah, Hidayat (Jurnal TUNAS, 2024)
AbstractYPAC Special School Pangkalpinang Bangka Belitung Islands Province provides educational services at the Special Elementary School, Special Junior High School and Special Senior High School levels. It is one of the private schools for children with special needs. With various types of developmental and growth disorders for children who have difficulty in following the learning process due to physical, emotional, mental, and social disorders, but they have the potential for intelligence and special talents, so the role of this Special School is vital in providing education for children with special needs. Currently, YPAC Pangkalpinang Special School teachers must still be competent in applying digital-based methods. With such situations and conditions, what is no less important is the need for active, creative, and innovative teachers with skills that always follow the development of the times. The skills teachers possess will make the school institution more advanced, especially in forming the school's vision and mission that are increasingly recognized in the community and have students with extraordinary skills and creativity like normal children in general. This is very important in providing skills education that can explore all the potential students have even though they have some limitations. Disability does not mean an obstacle for children with special needs to work and be creative in art, sports or other fields. By being given high enthusiasm and motivation, children who are usually often sidelined in society can make achievements with their creativity. Creativity will emerge if the child has the opportunity to gain knowledge. He learns many things so that new ideas will emerge for creativity.